2017
DOI: 10.1038/leu.2017.204
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of t(11;14) multiple myeloma

Abstract: Translocation (11;14) on interphase fluorescent in situ hybridization in plasma cells is regarded as a standard risk prognostic marker in multiple myeloma based on studies conducted before introduction of current therapies. We identified 365 patients with t(11;14), and 730 matched controls:132 patients with non-(11;14) translocations and 598 patients with no chromosomal translocation. The median progression-free survival for the three groups were 23.0 (95% confidence interval (CI), 20.8-27.6), 19.0 (95% CI, 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 30 publications
10
77
2
Order By: Relevance
“…In a recent retrospective analysis from the Mayo Clinic, Lakshman et al [4] reported that outcomes of patients with t (11;14) MM were inferior to those of other standard-risk patients. In their recent analysis of the Connect MM registry, Gasparetto et al [15] identified t (11;14) as an independent negative prognostic factor for OS (P = .009) and PFS (P = .073) in African American patients (n = 53); however, they found no such association between t (11;14) and PFS or OS in non-African American patients (n = 310).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent retrospective analysis from the Mayo Clinic, Lakshman et al [4] reported that outcomes of patients with t (11;14) MM were inferior to those of other standard-risk patients. In their recent analysis of the Connect MM registry, Gasparetto et al [15] identified t (11;14) as an independent negative prognostic factor for OS (P = .009) and PFS (P = .073) in African American patients (n = 53); however, they found no such association between t (11;14) and PFS or OS in non-African American patients (n = 310).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple myeloma (MM) with t (11;14) is classified into the standard risk category according to the International Myeloma Working Group (IMWG) and Mayo Clinic criteria [1,2]. However, recent reports have shown that the prognosis for MM with t (11;14) falls between that for MM without t (11;14)/t (4;14)/t(14;16)/del 17p and that for MM with t(4;14)/t(14;16)/ del 17p [3,4]. Furthermore, additional chromosomal abnormalities (ACAs) detected by G-banding, except for nonhypodiploid and del (13) [5], are excluded from the IMWG and Mayo Clinic criteria, and many US hospitals no longer perform cytogenetic analyses to evaluate the metaphase (Dr Shaji Kumar, Mayo Clinic, e-mail, 12 July 2018; with written permission) despite their recommendation by the National Comprehensive Cancer Network Guidelines in Oncology version 1.2019, and to date no studies have determined the prognosis of patients with MM harboring t (11;14) with or without ACAs, as identified on G-banding.…”
Section: Introductionmentioning
confidence: 99%
“…74 This is particularly noteworthy because MM patients with this genetic identifier are known to respond poorly to standard anti-myeloma therapies. 75 Significantly, a subsequent phase I trial (ClinicalTrials.gov identifier, NCT01794520) of venetoclax monotherapy in heavily pretreated RRMM patients, receiving 1200 mg/d, found that 12 of the 14 patients (of a total of 166 evaluable patients) who exhibited an objective response had the t(11;14) myeloma cell subtype. 76 A follow-up phase Ib trial (ClinicalTrials.gov identifier, NCT01794507) of 66 RRMM subjects combining venetoclax with bortezomib and dexamethasone found the combination to be well-tolerated, although no major difference in ORR attributable to t (11;14) biomarker status was observed (78% with the marker and 65% without).…”
Section: Apoptosis Inducers: Bcl-2 Iap and Mcl-1 Inhibitorsmentioning
confidence: 99%
“…The results obtained in the present study might be especially impactful, because MM patients with this chromosomal aberration have been shown to exhibit poorer outcomes compared with standard-risk myeloma patients. 75 Two other oral agents that have attracted clinical scrutiny for MM are selinexor and its second-generation relative eltanexor. The former entered a phase III study (the BOSTON trial [bortezomib, selinexor, and dexamethasone in patients with multiple myeloma]) in 2017.…”
Section: Summary and Future Prospectsmentioning
confidence: 99%
“…t (11,14)(q13; q32) is a commonly detected aberration; it is found in up to 20% of newly diagnosed patients with MM. Although the presence of t (11,14)(q13;q32) stratifies patients as having standard risk disease, the response rates and overall outcomes in these patients appear to be inferior to those of their other standard risk counterparts [2][3][4][5]. Typically, t (11,14)(q13;q32) has been associated with lymphoplasmacytic morphology and increased number of circulating plasma cells (PCs) [6].…”
Section: Introductionmentioning
confidence: 99%